Uji Instrumen Penilaian Mata Pelajaran Pendidikan Pancasila Kelas XI SMA - Lilis Muhlishah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Before a teacher uses a test, the teacher should first measure the degree of validity based on certain criteria. The aim of the research carried out was to determine the validity, reliability and level of difficulty of the Citizenship Education subject questions at the Class XI High School level which uses the Merdeka Curriculum as a reference. This research is part of development research with a 4D model, namely at the Develop stage. The process carried out is a simulation of questions on research subjects to determine the validity, reliability and level of difficulty of the questions being developed. The validity test of the questions showed that 25 questions were valid and 5 questions were invalid, while the reliability test showed that the questions had very high reliability. The instrument developed has a difficulty level of questions, namely 22 questions in the medium category, 6 questions in the easy category, and 2 questions in the difficult category.